JOB SATISFACTION AS A MEDIATION OF TRANSFORMATIONAL LEADERSHIP STYLE ON EMPLOYEE PERFORMANCE IN THE FOOD INDUSTRY IN MALANG CITY - Kenny Roz (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2019)
This research was conducted with the aim of testing the variable job satisfaction that mediated the effect of transformational leadership styles on employee performance in the food industry in Malang. The company guides each employee to improve their work performance. Leadership and satisfaction in work perceived by employees are considered to have a good impact on improving employee performance. This study uses a quantitative approach with a survey method. In this study using a saturated sample of 80 respondents were employees who were workers in food industry companies. The tool analysis in this study uses Partial Least Square (PLS). The results of this study, it was found that transformational leadership style and job satisfaction had a positive and significant influence on employee performance, and job satisfaction was able to mediate a positive relationship between transformational leadership scores on employee performance in the food industry in Malang.